Fluency and Accuracy in The EFL Oral Expression and Comprehension classroom - Soraya, Cherrad (The Explora, 2024)
Speaking the target language is often defined by both EFL students and teachers as the principle objective of language learning. However, all foreign language teachers recognise that, this is in fact, one of the most difficult skill to develop, giving that the aim of speaking is hindered by many factors resulting in most being reticent and unforthcoming when asked to speak the target language. Thus, EFL students may have difficulty in speaking fluent and accurate English. The present research took place at Djillali Liabes University of Sidi Bel Abbes (Algeria), exactly in English as a foreign language oral classes. It aims at analysing learners' attitudes in the EFL oral expression and comprehension classroom as well as to detect whether the focus on accuracy could hinder the practice of oral communication as well as cause problems in learning..Thus, both classroom observations and an interview were chosen as tools for data collection. Since the aim of language learning is to enhance EFL learners’ oral proficiency, this paper aims to highlight the value of both fluency and accuracy in the EFL oral expression classroom, for the latter to be reached.